Study on characterization of sandstone pore structure and seepage mechanism based on NMR and CT technology - Songxin Zhao; Kaide Liu; Chaowei Sun; Wenping Yue; Qiyu Wang; Yu Xia; Xinping Wang (PLoS ONE, 2026)
Coal-seam roof water disasters severely constrain safe and high-efficiency coal production. Integrating NMR, X-CT, Avizo, Netfabb, and Comsol, we systematically characterized pore architecture and flow behavior for the coarse, medium, and fine sandstones of the Luohe Formation in the Gaojiapu coal mine, Huanglong Jurassic coalfield, Ordos Basin. Results show that the NMR cumulative porosity of coarse, medium, and fine sandstones is 14.36%, 17.82%, and 16.09%, respectively; NMR permeability is 38.77 mD, 1.46 mD, and 0.87 mD; the proportions of macropores and micro-fractures are 48% and 27%, 34% and 12%, and 46% and 8%; fully movable porosity accounts for 68%, 42%, and 29%; NMR-connected pore fractal dimensions are 2.847, 2.943, and 2.955; CT total porosity is 16.43%, 15.51%, and 14.68%; CT connected porosity is 16.19%, 15.21%, and 14.36%; connectivity is 98.54%, 98.07%, and 97.82%; mean pore diameter is 17.50 μm, 17.16 μm, and 17.03 μm; mean throat radius is 32.63 μm, 29.11 μm, and 28.75 μm; absolute permeability is 10.88 D, 10.56 D, and 8.40 D; tortuosity is 1.63, 1.65, and 1.69. Flow-field simulations indicate that velocities below 0.08 m/s dominate, covering 80.14% in coarse sandstone and 97.54% in fine sandstone, providing a theoretical basis for roof water-hazard prevention.